Child-centred justice (Academic Journal of Internal Affairs, 2020)
What can this more and more frequently asserted new phrase mean? Is this a new slogan to be advertised at many places? The importance of the age can be observed from the beginning of the legislation just like the special role of the child in societies. At the same time, we meet pitfalls and uncertainties at the level of applicable procedural rules. There is a need of knowledge of some fundamental provisions of the procedural and substantive rules of criminal and civil law, bearing in mind within the scope of interpretation the legal principles established by international treaties, so that the phrase would not mean only a cliché. It is important to make it clear who can be regarded as a minor, what can be done by a child in person and what are the rules of representation, because every decisionmaker was a child once and the procedural legality depends on the compliance of the rules applicable to children.
Keywords: representation; child custody; the best interest of the child; procedural law